Main Mechanisms of Celestial Bodies Negative Polarization Formation: A Review - Petrov, Dmitry (Earth and Planetary Science, 2023)
The scattered light by the vast majority of celestial bodies without atmospheres has a characteristic feature: A negative branch of linear polarization degree at little phase angles. Researchers have proposed many theoretical mechanisms to explain this feature. This review describes the main mechanisms that form a negative branch of linear polarization degree. The results of ground-based observations of the negative branch of the degree of linear polarization of various objects of the solar system are described. Scattering by single particles, shadow effect, coherent backscattering enhancement, and effects of the near field are considered. The review will be useful for all researchers studying the scattering of light by celestial bodies. ER